2017
DOI: 10.3168/jds.2016-11700
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Outbreak of methicillin-resistant Staphylococcus aureus (MRSA)-associated mastitis in a closed dairy herd

Abstract: Cows are probably the main source of contamination of raw milk with Staphylococcus aureus. Mammary glands with subclinical mastitis can shed large numbers of Staph. aureus in milk. Because of the risk of this pathogen to human health as well as animal health, the aim of this paper was to describe an outbreak of mastitis caused by methicillin-resistant Staph. aureus (MRSA), oxacillin-susceptible mecA-positive Staph. aureus (OS-MRSA), and methicillin-susceptible Staph. aureus (MSSA) on a dairy farm. Milk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 28 publications
7
61
1
8
Order By: Relevance
“…A relatively higher prevalence (54%) of S.aureus was recorded by Berchtold et al (2014). Moreover, a higher prevalence (49.3%) was also recorded in Zimbabwe by Katsande et al (2013),in South Ethiopia (51.2%) by Abebe et al (2016), and in Brazil (53%) by Guimarães et al (2016). However, lower prevalence than the present findings was reported by many authors all over the world Wang et al 2014;Wang et al 2016).…”
Section: Discussioncontrasting
confidence: 47%
“…A relatively higher prevalence (54%) of S.aureus was recorded by Berchtold et al (2014). Moreover, a higher prevalence (49.3%) was also recorded in Zimbabwe by Katsande et al (2013),in South Ethiopia (51.2%) by Abebe et al (2016), and in Brazil (53%) by Guimarães et al (2016). However, lower prevalence than the present findings was reported by many authors all over the world Wang et al 2014;Wang et al 2016).…”
Section: Discussioncontrasting
confidence: 47%
“…From a total of 103 cows investigated, 12.2% of the mastitis cases were caused by S. aureus. In this collection of isolates, mecA was also detected in isolates that did not express the resistance phenotype (OS-MRSA-oxacillin-susceptible mecA-positive S. aureus) [119]. Haubert et al (2017) reported MRSA isolation, identified by phenotypic methods, in herds from the Rio Grande do Sul State (S).…”
Section: Staphylococcus Aureus and Other Staphylococcus Sppmentioning
confidence: 93%
“…They detected neither the mecA nor the mecC genes among the isolates [101]. Guimarães et al (2017) reported an outbreak of MRSA intramammary infections in Dutch cows from a dairy herd in São Paulo (SE). From a total of 103 cows investigated, 12.2% of the mastitis cases were caused by S. aureus.…”
Section: Staphylococcus Aureus and Other Staphylococcus Sppmentioning
confidence: 99%
“…In addition to lactic acid bacteria, other microorganisms were evaluated in the present study; these may have originated from cases of mastitis, a common disease in high production animals (such as those in dairy farms) and include Staphylococcus (Felipe et al, 2017;Guimarães et al, 2017), Streptococcus (Taponen et al, 2017), and Aerococcus (Saishu et al, 2015).…”
Section: Ggytaccttgttacgacttmentioning
confidence: 99%